Peranan Sahabat Bilal Bin Rabah Dalam Perjuangan Dakwah Rasulullah SAW - Annisa seftian Asti; Nicky Estu Putu Muchtar (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
Bilal bin Rabbah was one of the friends who played a very important role during the Da'wah struggle of Rasulullah SAW, and his struggle has provided a role model for all mankind in the world, especially for Muslims. In presenting this data used descriptive analysis research method. This study aims to find out, describe and analyze how the role of Bilal Bin Rabah in the Da'wah struggle of the Messenger of Allah. In the results of this study, it discusses the various important roles of Bilal bin Rabah in Islamic history. Bilal became a slave figure who was always tortured but remained persistent and obedient and always loyal to Rasulullah SAW until his death. Bilal was the first figure to become the first muezzin to call to prayer and was an important figure in the Badr war. In the Battle of Badr, he managed to kill his former employer, Umayyah bin Khalaf. Bilal had the advantage of having his faith tested through very sadistic torture but remained firm in his stance to embrace Islam. It is hoped that the results of this study can provide information regarding the role of Bilal Bin Rabah in the Da'wah struggle of the Prophet Muhammad, in emulating Bilal bin Rabah's courage, patience, and sincerity so that he can become an inspiration in everyday life.